Dual gold catalysis: [sigma], π-propyne acetylide and hydroxyl-bridged digold complexes as easy-to-prepare and easy-to-handle precatalysts - Hashmi, A. Stephen K.; Lauterbach, Tobias; Nösel, Pascal; Larsen, Mie Højer; Rudolph, Matthias; Rominger, Frank (Chemistry - a European journal, 2013)
A series of dinuclear gold σ,π-propyne acetylide complexes were prepared and tested for their catalytic ability in dual gold catalysis that was based on the reaction of an electrophilic π-complex of gold with a gold acetylide. The air-stable and storable catalysts can be isolated as silver-free catalysts in their activated form. These dual catalysts allow a fast initiation phase for the dual catalytic cycles without the need for additional additives for acetylide formation. Because propyne serves as a throw-away ligand, no traces of the precatalyst are generated. Based on the fast initiation process, side products are minimized and reaction rates are higher for these catalysts. A series of test reactions were used to demonstrate the general applicability of these catalysts. Lower catalyst loadings, faster reaction rates, and better selectivity, combined with the practicability of these catalysts, make them ideal catalysts for dual gold catalysis.